Observasi Pengelolaan Perpustakaan Daerah di Kabupaten Ngawi - Mareta Happy Prihani; Cindy Eka Rosita; Enessia Vida (Universitas PGRI Madiun, 2026)
This study aims to assess the actual state of governance, facility availability, and levels of public visitation and reading interest through an observational study at the Ngawi Regency Library. A descriptive-qualitative method was employed, utilizing data collection techniques such as direct observation, brief interviews with library staff, and documentation review. The observations indicate that the Ngawi Regency Regional Library possesses adequate infrastructure and has begun implementing digital services, such as an e-catalog and a digital reading area. However, certain persistent challenges remain, notably an unstable internet connection. Furthermore, daily visits are predominantly made by school and university students during specific hours, while participation from the general public remains low.